The Role Of Brand Image In Mediating The Influence Of Green Products On Purchasing Decisions (A Study On Consumers Of Pt. Work By Pak Oles Soccer) - Ketut Wahyu Tamaja; Ni Made Rastini; Ni Ketut Seminary; Komang Agus Satria Pramudana (PT Publikasiku Academic Solution, 2024)
Environmental damage caused by non-recyclable materials is an opportunity for business people to create environmentally friendly products. This study aims to explain the influence of green products on purchasing decisions, the influence of green products on brand image, the influence of brand image on purchase decisions, and the role of brand image in mediating the impact of green products on the purchase decision of PT. Karya Pak Oles Tokcer. The method of determining the sample in this study is non-probability sampling using the purposive sampling technique so that the sample involved in the study is 100 people. The analysis techniques used are path analysis and mediation role testing. The results show that green products have a positive and significant effect on purchasing decisions; Green products have a positive and significant impact on the brand image; the brand image has a positive and significant effect on product purchase decisions; the Brand image can mediate part of the influence of green products on purchasing decisions. The practical implications of this research can make a valuable contribution to the management of PT. Mr. Oles Tokcer in improving consumer purchasing decisions for PT. Karya Pak Oles Tokcer.